Economic Analysis of Music Copyright : Income, Media and Performances - Pitt, Ivan L. (Springer New York, 2010)
The first part is a general introduction to the many supply and demand economic factors that are related to music performance royalty payments. The second part is an applied econometrics section that provides modeling and in-depth analysis of income data from a songwriter, music publisher and blanket licensing perspective. In an era of declining income from CD album sales, data collection, mining and analysis are becoming increasingly important in terms of understanding the listening, buying and music use habits of consumers. The economic impact on songwriters, publishers, music listeners, and Performance Rights Organizations (PROs) is discussed and future business models are evaluated. The book will appeal to researchers and students in cultural economics, media and statistics as well as general readers and professionals in the music publishing industry